“I know I'm not going to have to heal from this”: Women university workers' collective writing on “office housework” as a space for building collective care, healing, and hope - Chatrakul Na Ayudhya, Uracha; Kunter, Aylin; Harley, Kayleigh Woods; Edwards, Isobel; Molyneaux, Sarah; Nicholas, Holly; Habib, Isabelle; Sheath, Janet (Gender, work, and organization, 2025)
How can we, as women university workers, assert collective writing as a form of resistance to embody our collective and individual struggles and convert them into words? We are a collective of five professional service and three academic women workers who came together to answer this question through writing about our performance of office housework and the gendered invisibility we experienced. We share our collective writing practices as a methodology to create connections and healing between workers divided along neoliberal and patriarchal university structures. Our work offers feminist epistemic resistance through the intentional joining of women university workers as co‐producers of knowledge, following the tradition of feminist consciousness‐raising groups. Our analysis problematizes the individualization of office housework. It illustrates how saying “no” individualistically is often elusive, because doing so displaces the work onto colleagues with less structural power; nor enough if we are to advance the goal of collectively reimagining how this crucial, yet invisible work can be redistributed more equally amongst all workers. Our collective writing affirms the need for office housework to be recognized and revalued as important and indispensable work that sustains the functioning of our higher education institutions, especially in times of uncertainty and crisis.